Etika Muhammadiyah & spirit peradaban / Zakiyuddin Baidhawy, Azaki Khoirudin; penyunting, Lia Novianti - ZAKIYUDDIN BAIDHAWY; AZAKI KHOIRUDIN; LIA NOVIANTI (Suara Muhammadiyah, 2017)
xxxviii, 488 hlm. : ilus. ; 23 cm.